BULLYING IN THE STUDY OF LEGAL SOCIOLOGY - Tabita Denes Febrian; Catharina Dewi Wulansari (CV. RADJA PUBLIKA, 2025)
The sociology of law is the study of the reciprocal relationship between law and society. It is a branch of science that studies, observes, and explains, using an empirical analytical approach, legal issues confronted with other phenomena in society. The sociological approach of law shows us that state law is not the sole guideline for behavior. In reality, other laws are effectively obeyed by society. Based on the Indonesian constitution, Article 31 Paragraph 3 of the 1945 Constitution, the government is obliged to manage and organize a national education system to foster faith and noble morals. Regarding bullying, which is a long-standing phenomenon that practically occurs in students' lives, perpetrators will continually intimidate and ridicule their peers. This must be stopped because it can cause victims to hinder class attendance. From a sociological perspective, any violence constitutes abusive behavior. Therefore, the enforcement of ethics generally stems from self-awareness. This situation seems very critical to eradicate, especially in the field of education, which has been systematically carried out outside the framework of the legal approach.